2016
DOI: 10.1017/s0021859616000460
|View full text |Cite
|
Sign up to set email alerts
|

The challenges and opportunities for wheat production under future climate in Northern Ethiopia

Abstract: SUMMARYWheat is an important crop in the highlands of Northern Ethiopia and climate change is expected to be a major threat to wheat productivity. However, the potential impacts of climate change and adaptation on wheat yield has not been documented for this region. Wheat field experiments were carried out during the 2011–2013 cropping seasons in Northern Ethiopia to: (1) calibrate and evaluate Agricultural Production Systems sIMulator (APSIM)-wheat model for exploring the impacts of climate change and adaptat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 44 publications
(107 reference statements)
5
33
0
Order By: Relevance
“…In Ethiopia for example, there is a growing realization that trees are important and linked to many biophysical processes including for regulating temperature and rainfall regimes (Muluneh et al, 2017b) and for crop buffering (Kassie, 2018;Sida et al, 2018). This is even more important with increasing risks of climate change on crop production (Araya et al, 2017;Bedeke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In Ethiopia for example, there is a growing realization that trees are important and linked to many biophysical processes including for regulating temperature and rainfall regimes (Muluneh et al, 2017b) and for crop buffering (Kassie, 2018;Sida et al, 2018). This is even more important with increasing risks of climate change on crop production (Araya et al, 2017;Bedeke et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…With the passage of time, advancements in these technologies have eased up genome-wide analyses among different organisms by using Bioinformatics databases and tools. Similar struggle was done for the sake of wheat improvement, which have been highly susceptible to numerous stresses such as insects, rusts, and climate change, since the very beginning and gradually shifted toward molecular breeding [19]; while, the most serious challenge is to fulfill the demand with continuously increasing consumption. In past, marker-assisted breeding had been used extensively for getting the desired manipulative task done; but with the amendments in biosafety and bioethics, most of the research has been directed toward marker-free technology.…”
Section: Challenges In Wheat Production Before and After Genomics Eramentioning
confidence: 94%
“…Impact of climate change has been assessed for the present and future. It has been indicated that there will be a climate change variability in the future (2030 and 2050) which will have a substantial impact on crop growth and productivity [6,7]. For example, studies on climate change projection in at different sites in Ethiopia indicate that there is an increase in maximum and minimum temperature in the future [6,7].…”
Section: Journal Of Climatology and Weather Forecastingmentioning
confidence: 99%
“…It has been indicated that there will be a climate change variability in the future (2030 and 2050) which will have a substantial impact on crop growth and productivity [6,7]. For example, studies on climate change projection in at different sites in Ethiopia indicate that there is an increase in maximum and minimum temperature in the future [6,7]. Future climate will depend on committed warming caused by past anthropogenic emissions, as well as future anthropogenic emissions and natural climate variability.…”
Section: Journal Of Climatology and Weather Forecastingmentioning
confidence: 99%
See 1 more Smart Citation